Arti Strategis Pulau Penyengat Sebagai Pulau Pertahanan - Repelita Wahyu Oetomo (Berkala Arkeologi Sangkhakala, 2010)
AbstractAt first, Penyengat Island is merely an island that visited by sailor for taking fresh water supply. In the subsequent period, given the strategic significance of the island was later used as a defense of the island. At a very critical condition, it threatens the existence of the Kingdom of Riau, the island is even used as a center of the kingdom but eventually as the collapse of Riau authority, the island was eventually abandoned.